Revelation and reason: a brief account of the contributions of some contemporary Muslim scholars - Hassan, Nur Jannah (Bangladesh Institute of Islamic Thought, 2017)
Secular humanism and atheistic-modernism left Muslims with the legacy of a dichotomous education. The dichotomy persists and today it is compounded by the onslaught of globalisation of post-modern thoughts shaping young minds. The melee of modern and post-modern worldviews has brought about grave environmental, civilisational and humanitarian crises. In response, many scholars have spent their lifetime in attempting to redress the situation, through what is generally considered as efforts of integration. They have conceived of integration as an organic fusion between revelation and reason and forged ahead with various attempts at integration. The article presents a brief survey on the integration efforts carried by 8 contemporary key Muslim figures, with an account of the thoughts of al-Ghazālī as precedence. Based on information gained from existing literature, the study found astute crystallisation and systematisation of integration especially in the works of later contemporary scholars.